Utility of Indocyanine Green Angiography for Preventing Pre-expanded Extended Lower Trapezius Myocutaneous Flap Necrosis: How to Make the Correct Decision for Hypoperfused Areas - Wang, Miao; Zang, Mengqing; Zhu, Shan; Chen, Bo; Li, Shanshan; Han, Tinglu; Chen, Zixiang; Liu, Yuanbo (Journal of Reconstructive Microsurgery, 2022)
Background Designing a skin flap that perfectly covers the anatomical and dynamic territories is challenging. Tissues capturing territories beyond may be insufficiently perfused, and these hypoperfused areas can lead to partial flap necrosis. Indocyanine green angiography (ICGA) is an effective tool for identifying hypoperfused areas. This retrospective study proposes a standardized strategy for managing the hypoperfused areas identified by ICGA in pre-expanded extended lower trapezius myocutaneous (e-LTMC) flaps.Methods Patients who underwent pre-expanded e-LTMC flap surgery with perfusion assessment using ICGA between June 2016 and January 2022 were identified. A standardized protocol was applied, and patients were divided into four groups according to different management options for hypoperfused areas detected by ICGA. Preoperative and operative variables of interest and postoperative outcomes, including flap necrosis and flap survival length, were collected and analyzed.Results Sixty-nine flaps were included in the study. No total flap necrosis was observed. Partial necrosis occurred in 10 flaps. Significant differences were observed in the incidence of full-thickness necrosis between the management groups. The incidence of flap necrosis in cases where management relied on ICGA findings was significantly lower than that of cases where management did not rely on ICGA findings. There were no differences in the relative survival length of the flap between cases with and without intervention for the hypoperfused areas.Conclusion The proposed standard strategy effectively reduced the necrosis rate of the pre-expanded e-LTMC flap, thus it is sensible to act on the ICGA findings. Prophylactic resection of the hypoperfused area should be recommended. Where resection may lead to poor reconstructive outcomes, flap trimming or a second flap should be the preferred option.
Keywords: indocyanine green angiography; flap necrosis; hypoperfused area